2009
DOI: 10.1179/oeh.2009.15.3.318
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Leukemia and Cancers Near German Nuclear Reactors: Significance, Context, and Ramifications of Recent Studies

Abstract: *Conventionally, statistical significance for increased RR > 1.00 is expressed either by a p < 0.05 for RR or a lower limit > 1.00 in a 95% confidence interval. Both statistical measures indicate that there is more than a 95% probability that the RR for an exposed population is significantly elevated or the equivalent statement, that there is less than a 5% probability that a RR > 1.00 is a chance result. Instead of RR, in case control studies odds ratios (OR) are used to express relative risk with comparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In this Table 1 and Mathews and Hamilton (2005) Fig. 1 Trends of the live births sex odds (male/female) in Europe and in the USA, 1950to 1990(Martuzzi et al 2001Mathews and Hamilton 2005) (Spix et al 2008;Nussbaum 2009). A sensitivity analysis displacing all nuclear facilities' original geographic positions 50 km to the west or 50 km to the east yields insignificant (p>0.5) Rayleigh functions (Fig.…”
Section: Further Evidence: Increased Sex Odds Near Nuclear Facilitiesmentioning
confidence: 84%
“…In this Table 1 and Mathews and Hamilton (2005) Fig. 1 Trends of the live births sex odds (male/female) in Europe and in the USA, 1950to 1990(Martuzzi et al 2001Mathews and Hamilton 2005) (Spix et al 2008;Nussbaum 2009). A sensitivity analysis displacing all nuclear facilities' original geographic positions 50 km to the west or 50 km to the east yields insignificant (p>0.5) Rayleigh functions (Fig.…”
Section: Further Evidence: Increased Sex Odds Near Nuclear Facilitiesmentioning
confidence: 84%
“…DOI 10.1002/em dose occupational radiation exposure to ionizing radiation may have substantial detrimental effects on functional, genetic, and epigenetic sperm integrity in health workers (Kumar et al 2013). However, from an epidemiological perspective, the findings are scanty, limited by sample size, heterogeneous nature of medical and medical (professional and diagnostic) exposures, and low incidence of events (Altman and Bland 1985;Savitz et al 1989;Correa-Villasenor et al 1993;Shea and Little 1997;Parker et al 1999;Shakhatreh 2001;Nussbaum 2009). Only one small study on the contemporary population of cardiac cath lab staff on 90 exposed male radiographers (and 90 unexposed controls) reported a striking increase in risk (with relative risks ranging from 2 to 10) in reproductive health problems (Shakhatreh 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, no plausible (genetic) explanations have been proposed to date for these clusters, and because of a lack of knowledge regarding the biological mechanism behind these observations, it was concluded that there were “no indications” for an increased risk of childhood cancer [79]. But, in his critical report [82], Nussbaum rightfully reminded epidemiologists that they should not ignore a fundamental rule earlier espoused by Altman and Bland [83], “The absence of evidence of an effect does not constitute evidence of absence of that effect.”…”
Section: Do Paternal Exposures To Low Dose Ionizing Radiation Promotementioning
confidence: 99%